Mullā Ṣadrā’s Ontology: The Fundamentality of Existence Over Essence - Muhammad Faiq; Ibnu Farhan (Fakultas Ushuluddin dan Dakwah Institut Al Fithrah Surabaya, 2023)
One of the critical debates in the philosophical tradition is about existence and essence. The question that arises from this problem is which of the two is more principle or fundamental. Some Muslim philosophers have different points of view regarding this. This article aims to reveal Mullā Ṣadrā's thoughts on the fundamentality of existence. This study is qualitative research with a descriptive and analytical approach. The data were collected from library research. This study found that, in Mullā Ṣadrā’s viewpoint, existence is more fundamental than essence as it causes essence to exist. Mullā Ṣadrā's view leads to the solving of many philosophical problems, such as the problem of causality, Tawhid, the impossibility of the concept of predestination, and dualism, for instance, heaven and hell, world and hereafter, Khaliq and creature, God and universe, material and non-material, transcendent and immanent Salah satu perdebatan serius dalam tradisi filsafat adalah tentang eksistensi dan esensi. Pertanyaan yang muncul dari persoalan ini adalah mana di antara keduanya yang lebih prinsipil atau fundamental. Para filosof Muslim memiliki pandangan yang berbeda mengenai hal ini. Studi ini bertujuan mengungkap pemikiran Mullā Ṣadrā tentang keutamaan eksistensi. Studi ini merupakan penelitian kualitatif dengan pendekatan deskriptif dan analitis. Data dikumpulkan dari studi kepustakaan. Studi ini mengungkap bahwa menurut Mullā Ṣadrā, eksistensi lebih utama/real ketimbang esensi karena eksistensilah yang menjadikan esensi itu ada/wujud. Pandangan Mullā Ṣadrā ini penting untuk pemecahan beberapa persoalan filosofis, seperti masalah kausalitas, tauhid, kemustahilan konsep predestinasi dan dualisme, misalnya surga dan neraka, dunia dan akhirat, khaliq dan makhluk, Tuhan dan alam semesta, material dan non-material, transenden dan imanen.